Characterization of protein glycosylation in an Asgard archaeon - Satoshi Nakagawa; Hiroyuki Imachi; Shigeru Shimamura; Saeko Yanaka; Hirokazu Yagi; Maho Yagi-Utsumi; Hiroyuki Sakai; Shingo Kato; Moriya Ohkuma; Koichi Kato; Ken Takai (BBA Advances)
Archaeal cells are typically enveloped by glycosylated S-layer proteins. Archaeal protein glycosylation provides valuable insights not only into their adaptation to their niches but also into their evolutionary trajectory. Notably, thermophilic Thermoproteota modify proteins with N-glycans that include two GlcNAc units at the reducing end, resembling the ''core structure'' preserved across eukaryotes. Recently, Asgard archaea, now classified as members of the phylum Promethearchaeota, have offered unprecedented opportunities for understanding the role of archaea in eukaryogenesis. Despite the presence of genes indicative of protein N-glycosylation in this archaeal group, these have not been experimentally investigated. Here we performed a glycoproteome analysis of the firstly isolated Asgard archaeon Promethearchaeum syntrophicum. Over 700 different proteins were identified through high-resolution LC-MS/MS analysis, however, there was no evidence of either the presence or glycosylation of putative S-layer proteins. Instead, N-glycosylation in this archaeon was primarily observed in an extracellular solute-binding protein, possibly related to chemoreception or transmembrane transport of oligopeptides. The glycan modification occurred on an asparagine residue located within the conserved N-X-S/T sequon, consistent with the pattern found in other archaea, bacteria, and eukaryotes. Unexpectedly, three structurally different N-glycans lacking the conventional core structure were identified in this archaeon, presenting unique compositions that included atypical sugars. Notably, one of these sugars was likely HexNAc modified with a threonine residue, similar to modifications previously observed in mesophilic methanogens within the Methanobacteriati. Our findings advance our understanding of Asgard archaea physiology and evolutionary dynamics.